Performance Persistence in Polish Mutual Funds - Staniszewski, Mariusz; Smolarek, Tomasz (Powtarzalność wyniku inwestycyjnego polskich funduszy akcji, 2010)
Many academic studies present strong evidence in favour of performance persistence in mutual fund industry. In this research we decided to examine if it is also true for mutual funds in Poland. We analyse 14 Polish equity funds that operated on the Polish market from 2002 to 2009. Tests are based both on net return and risk-adjusted measure (Jensen's alpha). Our results on the one hand do not confirm performance persistence of good results (hot hands phenomenon), particularly when longer time interval is considered (one year). On the other hand we prove icy hands phenomenon, both for short and long time interval.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 138, s. 131-141
Keywords: mutual funds; performance persistence; hot hands phenomenon; icy hands phenomenon